Determinants Of Stunting on Human Development and The Role Of The Government - Pinilih, Nada Septia; Putri, Wulandari Kartika; Arif, Muhammad (Economos : Jurnal Ekonomi dan Bisnis, 2024)
This study aims to evaluate various factors contributing to stunting in Central Java Province, including life expectancy, average years of schooling, per capita income, gender development index, and government assistance for the mother and child sector. Panel data is the type of data used in this study using a quantitative approach. The method used in this study is quantitative and uses panel data consisting of time seris and cross section data presented in one table. Central Java Statistics Agency is used as a reference data in this study called secondary data. Poor nutrition is the dependent variable used, while the independent variables used include Life Expectancy, Gender Development Index, Gross Regional Domestic Product, and Number of Family Hope Companion Recipients. Analysis using panel data regression by performing the Chow Test and Hausman Test to determine the best model is the analysis technique used. Then look at the relationship between the dependent variable and the independent variable and draw conclusions. The results showed that the Fixed Effect Model was the best model used in this study and showed that the number of stunting sufferers in Central Java was negatively and significantly affected by Life Expectancy (AHH) and Average School Year (RLS). Meanwhile, GRDP or Gross Regional Domestic Product and PKH or Family Hope Program have been proven to have a statistically positive relationship with the number of stunting sufferers in Central Java. Meanwhile, although the Gender Development Index (IPG) is negative, statistically it has not been able to affect the stunting rate in Central Java during the 2020-2022 period.